A model of service learning and outreach for primary education through museums - Mikelić Preradović, Nives (Array, 2014)
This paper presents a model for the development of collaborative projects between universities, institutions for primary education and museums. The project described in this paper was realized as a service learning project through collaboration between students of Information Sciences from the Faculty of Humanities and Social Sciences, Museum of Arts and Crafts and elementary school “Cvjetno naselje”. As a result, the Museum gained young experts and valuable help in its outreach mission, while university students expanded their practical experience working with the museum pedagogue and leading school classes through the Museum. The evaluation of the service learning project addressed the role of field experiences in university education, service learning pedagogy and museum education partnerships.